1998
DOI: 10.1076/apab.106.1.19.4390
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Osmotic Fragility in Bufo arenarum Exposed to Lead

Abstract: The effects on red blood cells of a single sublethal dose of Pb of 100 mg kg-1 administrated to adult Bufo arenarum were studied. The blood d-aminolevulinic acid dehydratase (d-ALAD) activity, the red blood cell (RBC) osmotic fragility (OF), and the hematocrit (Hct) were measured in control and lead poisoned toad. The enzyme d-ALAD is considered as a specific biomarker for human and animals lead exposure. In Bufo, lead also provoked a significant decrease in the d-ALAD activity without changes in the Hct. OF t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
1
3
0
3
Order By: Relevance
“…Similar observations were reported in tadpoles where the number of red cells diminished after exposure to the metal (Barret 1947). Lead is well known to act on hematopoiesis in amphibians Arrieta et al 2000;Rosenberg et al 1998Rosenberg et al , 2002 and elevated blood lead concentrations may be reflected in alterations of the morphology and the physiological properties of the circulating cells (Rosenberg et al 2003). Lead is also known to alter red blood cell membrane proteins in humans (Caspers & Siegel 1980) and to produce reactive oxygen species involved in the phagocytic process as a consequence of altered membrane integrity, permeability and lipid peroxidation mechanisms (Gurer & Ercal 2000).…”
Section: Acute Toxicity Genotoxicity and Lead Accumulationsupporting
confidence: 53%
“…Similar observations were reported in tadpoles where the number of red cells diminished after exposure to the metal (Barret 1947). Lead is well known to act on hematopoiesis in amphibians Arrieta et al 2000;Rosenberg et al 1998Rosenberg et al , 2002 and elevated blood lead concentrations may be reflected in alterations of the morphology and the physiological properties of the circulating cells (Rosenberg et al 2003). Lead is also known to alter red blood cell membrane proteins in humans (Caspers & Siegel 1980) and to produce reactive oxygen species involved in the phagocytic process as a consequence of altered membrane integrity, permeability and lipid peroxidation mechanisms (Gurer & Ercal 2000).…”
Section: Acute Toxicity Genotoxicity and Lead Accumulationsupporting
confidence: 53%
“…Lefcort et al (1998) reported that heavy metals could alter the survival, growth, metamorphosis and antipredatory behavior of Rana luteiventris tadpoles. Rosenberg et al (1998) studied the sublethal effect of lead on erythrocyte osmotic fragility in Bufo arenarum. Naab et al (2001) reported that Zn could inhibit the pentose phosphate pathway in the ovaries of adult B. arenarum females, resulting in a decrease of the embryo survival ratio.…”
mentioning
confidence: 99%
“…La actividad de la ALAD se determinó por duplicado de acuerdo a la técnica desarrollada en nuestro laboratorio, basada en el método Europeo Estandarizado (Berlin y Schaller, 1974;Perí et al, 1998). Los principales cambios introducidos en el ensayo consisten en el volumen de sangre utilizada y el pH de la reacción.…”
Section: 13-parámetros Bioquímicosunclassified
“…En otra serie de estudios previos, se demostró que la administración del metal en un corto período de tiempo (dosis única de AcPb), no provocaba cambios significantes en el hematocrito (Arrieta et al 2000;Perí et al 1998b;Rosemberg et al, 1998). Ireland (1977) obtuvo resultados coincidentes con éstos en Xenopus leavis adultos, evaluando hemoglobina, hematocrito y reticulocitos, los cuales no presentaron cambios significativos, con excepción de la actividad de la δ-ALAD que tuvo cambios con significancia estadística.…”
Section: 16-aspectos Adversos Del Plomo Sobre El Sistema Hematopoyunclassified
See 1 more Smart Citation